2005
DOI: 10.1074/mcp.m500203-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Quantitative Glycomics and Glycoform-focused Proteomics of Murine Dermis and Epidermis

Abstract: Despite recent advances in our understanding of the significance of the protein glycosylation, the throughput of protein glycosylation analysis is still too low to be applied to the exhaustive glycoproteomic analysis. Aiming to elucidate the N-glycosylation of murine epidermis and dermis glycoproteins, here we used a novel approach for focused proteomics. A gross N-glycan profiling (glycomics) of epidermis and dermis was first elucidated both qualitatively and quantitatively upon N-glycan derivatization with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
84
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 47 publications
(39 reference statements)
3
84
0
1
Order By: Relevance
“…Recent efforts toward decoding the glycome have focused on the use of mass spectrometry (4)(5)(6)(7)(8)(9). Although great strides have been made in the use of this technique, mass spectrometry has difficulty in discriminating between the many structural isomers presented by glycans.…”
mentioning
confidence: 99%
“…Recent efforts toward decoding the glycome have focused on the use of mass spectrometry (4)(5)(6)(7)(8)(9). Although great strides have been made in the use of this technique, mass spectrometry has difficulty in discriminating between the many structural isomers presented by glycans.…”
mentioning
confidence: 99%
“…These high-mannose type oligosaccharides are located in lysosomes, lamellar granules and cell-cell connection desmosome sites. Desmocollins and desmogleins are also assigned as carriers of high-mannose type oligosaccharides, and it was suggested that high-mannose type oligosaccharides control desquamation [24]. However, in the present samples of hyperkeratotic skin, the profile of the high-mannose type oligosaccharides was not changed.…”
mentioning
confidence: 58%
“…Alteration of N-glycan profiles in diseases have been reported in many human disorders, and these have been used for disease diagnosis and for elucidation of disease pathomechanisms [4,8]. Focusing on glycoproteins N-glycans, it was demonstrated that the mouse epidermis had abundant high-mannose oligosaccharides [24]. In addition, the oligosaccharides binding proteins were also determined [24].…”
mentioning
confidence: 99%
See 2 more Smart Citations